Efektivitas Perencanaan dan Realisasi Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (Pamsimas) di Desa Kemang Indah, Kabupaten Kampar - Khoirunnisa, Salsabila; Purba, Dea Natalia; Simanjuntak, Putri Christina; Putri, Annie Mustika (Asosiasi Dosen Akuntansi Indonesia, 2024)
The study aims to evaluate the effectiveness of planning and implementation of PAMSIMAS programs in Kemang Indah Village, Kampar District. Qualitative data is collected through in-depth interviews with informants, participatory observations, and focus group discussions. The research results show that the PAMSIMAS program in Kemang Indah Village has realized and improved access to drinking water and sanitation. Most villagers now have access to safe drinking water and adequate sanitation. The PAMSIMAS program in Kemang Indah Village has effectively improved access to drinking water and sanitation.